The legality of Dissecting the Human Body - El Hassan, Hala; Karim, Eman Fahd (Latakia University Journal - Economic and Legal Sciences Series, 2019)
Anatomy of the human body for criminal, medical or educational purposes is one of the most important contemporary medical issues that need to be examined to find out its legal and legal rulings, especially since anatomy is of great importance in our modern world. Almost no society in contemporary societies is free of anatomy at universities and medical schools. International and regional conventions enshrine the principle of inviolability of the human body. The Universal Declaration of Human Rights in Islam states: "The physical and moral entity of man is protected by law in his life and after his death, and he is entitled to be attached and honored in dealing with his body." Since the right to physical integrity is considered to be one of the close rights of the person who guarantees the legitimacy of the autopsy, where the sanctity of the human body extends beyond death, it was necessary to know the legal controls for the possibility of dissecting the human body. يعد تشريح جثة الإنسان لأغراض جنائية أو طبية أو تعليمية أحد أهم المسائل الطبية المعاصرة التي تحتاج إلى البحث لمعرفة حكمها من الناحية الشرعية والقانونية، وخاصة لما للتشريح من أهمية كبيرة في عالمنا المعاصر، إذ يكاد لا يخلو مجتمع من المجتمعات المعاصرة من إجراء التشريح في الجامعات والمدارس الطبية. كرست المواثيق الدولية والإقليمية مبدأ حرمة جثة الإنسان حيث نص البيان العالمي لحقوق الإنسان في الإسلام أن: " كيان الإنسان المادي والمعنوي حميٌ عزيز. تحميه الشريعة في حياته وبعد مماته، ومن حقه الترفق والتكريم في التعامل مع جثمانه ". و نظراً لاعتبار الحق في السلامة الجسدية وهو من الحقوق اللصيقة بالشخصية الضامن لمشروعية تشريح الجثة حيث تمتد حرمة الجسد البشري إلى ما بعد الموت, كان لا بد من معرفة الضوابط الشرعية والقانونية لإمكانية تشريح جثة الإنسان .